Theoretical Lower Limit of Coercive Field in Ferroelectric Hafnia - Jiyuan Yang; Jing Wu; Jingxuan Li; Chao Zhou; Yang Sun; Zuhuang Chen; Shi Liu (Physical Review X)
The high coercive field (E_{c}) of hafnia-based ferroelectrics presents a major obstacle to their applications. The ferroelectric switching mechanisms in hafnia that dictate E_{c}, especially those related to domain nucleation in the nucleation-limited-switching (NLS) model and domain-wall motion in the Kolmogorov-Avrami-Ishibashi (KAI) model, have remained elusive. We develop a deep-learning-assisted multiscale approach, incorporating atomistic insights into the critical nucleus, to predict both NLS- and KAI-type coercive fields. The theoretical NLS-type E_{c} values agree with previous experimental results as well as our own measurements and also exhibit the correct thickness scaling for films between 3 and 20 nm. Combined theoretical and experimental investigations reveal that the giant E_{c} in hafnia-based ferroelectrics arises from the ultrathin geometry, which confines switching to the NLS mechanism. We predict that the theoretical lower limit for KAI-type E_{c} is 0.1  MV/cm arising from mobile domain walls. The activation of KAI-type switching to achieve lower E_{c} is supported by our experimental demonstration of a low coercive field of 1  MV/cm in 60 nm ferroelectric (HfO_{2})_{n}/(ZrO_{2})_{n} (n=3 unit cells) superlattices. These findings establish a comprehensive framework for understanding ferroelectric switching in hafnia and highlight the potential of geometry and domain-wall engineering to achieve low-E_{c} devices.